Sustainable Investing for Institutional Investors : Risk, Regulations and Strategies - Staub-Bisang, Mirjam, 1969- (John Wiley & Sons, 2012)
A comprehensive guide to socially responsible investing (SRI)With concerns about climate change increasing among investors, many are looking for opportunities that offer positive social as well as monetary returns. Sustainable Investing for Institutional Investors: Risk, Regulation and Strategies explores the key issues related to "Socially Responsible Investment" (SRI) for institutional investors and trustees, including investment strategies, risk and returns, market data, regulatory frameworks, and more. Looking at all investment classes, including bonds, equities, real estate, commodities.